2011
DOI: 10.1890/10-0400.1
|View full text |Cite
|
Sign up to set email alerts
|

Volatile chemicals from leaf litter are associated with invasiveness of a Neotropical weed in Asia

Abstract: Some invasive plant species appear to strongly suppress neighbors in their nonnative ranges but much less so in their native range. We found that in the field in its native range in Mexico, the presence of Ageratina adenophora, an aggressive Neotropical invader, was correlated with higher plant species richness than found in surrounding plant communities where this species was absent, suggesting facilitation. However, in two nonnative ranges, China and India, A. adenophora canopies were correlated with much lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
124
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(126 citation statements)
references
References 49 publications
2
124
0
Order By: Relevance
“…The NWH hypothesis predicts selection for higher production of chemical(s) novel for the invaded community (Supplemental Box S1; Callaway and Ridenour, 2004). In a common garden experiment, Inderjit et al (2011b) reported that leaf litter from exotic populations of A. adenophora from China and India had higher emissions of 2-carene and a-phellandrene and lower emission of (E)-b-caryophyllene (EbC), b-pinene, (E)-a-bergamotene, and bicyclogermacrene compared to native Mexican litter. They also found that the inhibition of native species in the presence of invasive A. adenophora litter could be due to the biogeographic variation in volatiles from exotic or native litter.…”
Section: Nwhmentioning
confidence: 99%
See 4 more Smart Citations
“…The NWH hypothesis predicts selection for higher production of chemical(s) novel for the invaded community (Supplemental Box S1; Callaway and Ridenour, 2004). In a common garden experiment, Inderjit et al (2011b) reported that leaf litter from exotic populations of A. adenophora from China and India had higher emissions of 2-carene and a-phellandrene and lower emission of (E)-b-caryophyllene (EbC), b-pinene, (E)-a-bergamotene, and bicyclogermacrene compared to native Mexican litter. They also found that the inhibition of native species in the presence of invasive A. adenophora litter could be due to the biogeographic variation in volatiles from exotic or native litter.…”
Section: Nwhmentioning
confidence: 99%
“…NWH assumes that an exotic plant produces higher amounts of chemicals in introduced ranges (Inderjit et al, 2006). An exotic plant, however, produces certain compounds in higher amounts in its native range too (see Inderjit et al, 2011b). Biogeographic variation in defense versus allelopathic chemicals might give better insights into NWH.…”
Section: Nwhmentioning
confidence: 99%
See 3 more Smart Citations